PRSP processes in eight African countries: Initial impacts and potential for institutionalization - David Booth (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
An almost accidental by-product of the enhanced HIPC initiative, the process of producing poverty reduction strategy papers represents at least potentially a non-trivial change in the way international finance interacts with poverty reduction efforts at the national level. This paper reports the preliminary findings of a study commissioned by the Strategic Partnership with Africa (SPA) that considers early experiences with PRSPs in eight African countries: Benin, Ghana, Kenya, Malawi, Mali, Mozambique, Rwanda and Tanzania. The paper argues that politics matters; that PRSPs have helped bring poverty into the policy mainstream; that PRSPs depend on but also contribute something to wider structural reforms; and that the consultative processes around PRSPs could produce second-round effects of a beneficial kind. – poverty ; policy process ; political systems ; participation
Keywords: O19; F35; O55; 330; Armutspolitik; Afrika; Benin; Ghana; Kenia; Malawi; Mali; Mosambik; Ruanda; Tansania